Occupational Stress And Blood Pressure Among Online Motorcycle Taxi Drivers In Bandung: A Cross-Sectional Study - Indah Tiara Novelia; Herdiman, Herdiman (Medical-Surgical Journal of Nursing Research, 2025)
Background: Hypertension is a major global public health problem influenced by a complex interaction of biological, psychological, and social factors, including stress. Individuals working in the informal transportation sector, such as online motorcycle taxi drivers, are at increased risk of psychological stress due to employment uncertainty, extended working hours, and continuous exposure to traffic-related conditions. Objective: This study aimed to examine the relationship between perceived stress levels and blood pressure among online motorcycle taxi drivers in Bandung. Methods: A quantitative cross-sectional study was conducted with 147 respondents selected through random sampling. Data were collected using a demographic questionnaire, the Perceived Stress Scale (PSS-10), and blood pressure measurements obtained with a digital sphygmomanometer. Data analysis included univariate statistics and bivariate analysis using Spearman’s rank correlation and Chi-square tests. Results: The majority of participants were male (91.8%) with a mean age of 28 years, and 76.9% reported smoking. Most respondents experienced moderate stress (92.5%). Blood pressure assessment showed that 53.1% were categorized as prehypertensive and 40.1% as having stage 1 hypertension. Perceived stress was positively correlated with systolic (p < 0.001; r = 0.462) and diastolic blood pressure (p = 0.002; r = 0.258). Smoking behavior and hypertension history were also significantly associated with blood pressure levels. Conclusion: Perceived stress is significantly associated with elevated systolic and diastolic blood pressure among online motorcycle taxi drivers. These findings highlight the need for stress management and lifestyle-based interventions to reduce hypertension risk in informal-sector workers.